Pengaruh Produk, Tempat dan Promosi terhadap Kepuasan Pelanggan di Hotel Santika Depok - Annisa Febriyanti Safitri; Dona Fitria; Burhanudin Burhanudin (Departement of Mathematics Education, 2023)
This study aims to determine the effect of product, place, and promotion on customer satisfaction at Hotel Santika Depok through quantitative methods, including surveys and data collection through observation, questionnaires, and unstructured interviews. This study used a sample of 100 guests from Hotel Santika Depok, selected using incidental sampling. The total population of guests at the hotel over the last six months was 28,804. The data for this research was collected via questionnaire on the variables of product, place, promotion, and customer satisfaction. The data analysis technique used was multiple linear regression, with the correlation coefficient and coefficient of determination being calculated using SPSS tools. The results of this study suggest that product, place, and promotion have a positive and significant influence on customer satisfaction at Hotel Santika Depok. This is indicated by the multiple linear regression values, which show a correlation coefficient of 0.827 for the product variable, 0.850 for the place variable, and 0.890 for the promotion variable. The coefficient of determination is 84.3%. This means that product, place and promotion contribute 84.3% to customer satisfaction at Hotel Santika Depok, while the remaining 15.7% is influenced by other factors and variables not examined in this study. The results of the hypothesis testing showed that the F-test value was greater than the F-table value, indicating that the null hypothesis should be rejected in favor of the alternative hypothesis. The t-test also showed that the t-count value was greater than the t-table value for all three variables, indicating that the null hypothesis should be rejected for all three variables.